Elementary School Students’ Perceptions of the Future Environment through Artwork - Özsoy, Sibel; Ahi, Berat (Egitim Danismanligi ve Arastirmalari (EDAM), 2014)
The purpose of the present study is to investigate first level of elementary school students' perceptions of the future state of the environment through the pictures they draw. The participants of the study are 131 first-grade students, 127 second-grade students, 160 third-grade students, 188 fourth-grade students, and 222 fifth-grade students, totaling 828 students. The study used the survey method, one of the descriptive research methods, to collect data. More specifically, the draw-and-explain technique, in which participants were asked to draw a picture about the environment and then explain their drawings, was used to collect data. In the analysis of the data, both qualitative and quantitative data analysis methods were employed. When the data were analyzed, it was found that 28.5% of the students held perceptions of a clean future environment, that 40.3% held percep- tions of a polluted future environment, and 31.2% held perceptions of technological future environment. While a significant difference based on the region of residence and grade level was found in students' perceptions of the future state of the environment, gender did not yield a significant difference. The elementary school students' drawings mostly include elements such as trees, the sun, clouds, humans, birds, butterflies, houses, apartment buildings, mountains, seas, rivers, garbage, and dust bins. When the students' drawings were analyzed, it was found that the students mostly include environmental problems that they were more likely to see in their close environments, such as air pollution, soil pollution, over construction, and traffic. It was also found that students had a limited awareness of the types of pollution and of living and non-living organisms in the environment.
Keywords: Environmental Pictures; Elementary School Students; Perceptions of Environment; Students' Perceptions of Environment in Future; 13. Climate action; 4. Education; 11. Sustainability